Evaluasi pengaruh substitusi tepung pisang kepok (Musa × Paradisiaca L.) terhadap sifat organoleptik, preferensi konsumen, serta kandungan protein dan kadar air pada produk olahan Shiroi Koibito - Salanza Alfarest Darajat; Bambang Sugeng Suryatna (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2026)
Shiroi Koibito is a wheat flour-based cookie product that has a crispy texture but is low in fiber and local food ingredients. One alternative substitute ingredient that can increase nutritional value and utilize local commodities is plantain flour (Musa × paradisiaca L.). This study aims to evaluate the effect of plantain flour substitution on the organoleptic quality, consumer preference, and protein and moisture content of Shiroi Koibito products. The study used an experimental design with four treatments: F1 (100% wheat flour), F2 (75% wheat flour:25% banana), F3 (50%:50%), and F4 (25%:75%). Organoleptic tests include color, aroma, taste, texture, and overall assessment. Chemical tests include protein content and moisture content. Chemical tests included protein and moisture content. The results showed that treatment F3 (50:50) had the highest organoleptic score (8.19), producing a golden brown color, natural sweet aroma, and crispy texture. The protein content tended to decrease with increasing substitution of kepok banana flour, while the moisture content increased at high substitution (75%). The study concluded that 50% substitution of kepok banana flour produced the best sensory characteristics without significantly reducing chemical quality and had the potential to become an innovation in the use of local ingredients in the bakery industry.